At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Write a rule in coordinate form for the translation from Triangle EFG to Triangle
E'F'G'.
(x,y)-->(x+2, y-1)
(x,y)-->(x+1, y-2)
(x,y)-->( X-2, y + 1)
(x,y)-->(x+3, y +2)


Write A Rule In Coordinate Form For The Translation From Triangle EFG To Triangle EFG Xygtx2 Y1 Xygtx1 Y2 Xygt X2 Y 1 Xygtx3 Y 2 class=

Sagot :

Answer:

1st option

Step-by-step explanation:

Consider the coordinates of F and F'

F (- 3, 4 ) and F' (- 1, 3 )

To go from - 3 → - 1 in the x- directions , means adding 2

To go from 4 → 3 in the y- direction means subtracting 1

Then translation rule is

(x, y ) → (x + 2, y - 1 )